2015
DOI: 10.1002/masy.201550307
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of Platinum Particles in Bacterial Cellulose Membranes from PtCl4 and H2PtCl6 Precursors

Abstract: Summary The Pt nanoparticles have been synthesized in situ using bacterial cellulose (BC) membranes as the matrix. The BC was immersed in a solution of PtCl4 and H2PtCl6 as Pt(IV) precursors also in surfactant stabilized Multiwall Carbon Nanotubes (MWCNT) as carbon source. Then, the Pt(IV) was reduced by hydrogen gas. Two routes have been applied for the insertion Pt particles; in the first route the Pt particles were inserted before the insertion of MWCNT and in the second route the other way around was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In the next step, as-prepared BC-NBCNT membranes (100 mg) were impregnated by a 0.5 cm 3 20 wt% platinum solution (0.04 g H 2 PtCl 6 9 H 2 O in 0.5 cm 3 water). Two similar synthesis routes were published recently [7]. During the process, 0.25 cm 3 of platinum solution was added dropwise to both sides of the membranes.…”
Section: Membrane Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…In the next step, as-prepared BC-NBCNT membranes (100 mg) were impregnated by a 0.5 cm 3 20 wt% platinum solution (0.04 g H 2 PtCl 6 9 H 2 O in 0.5 cm 3 water). Two similar synthesis routes were published recently [7]. During the process, 0.25 cm 3 of platinum solution was added dropwise to both sides of the membranes.…”
Section: Membrane Preparationmentioning
confidence: 99%
“…To overcome limitations and to further improve the effectiveness of catalysts, many researchers have focused on the development of material-supported Pt catalysts. In this regard, carbon nanotubes (CNTs) [6] and bacterial cellulose (BC) [7] are of interest in the development of a novel hybrid membrane catalyst for a wide range of applications.…”
Section: Graphic Abstract Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The electrode used was BC coated Pt catalyst and carbon by way of brushing, and Pt catalyst performance has been analyzed with the PEMFC. Meanwhile, Aritonang et al [8] have been coating BC by immersion into a solution of Pt precursors and carbon powder. The results showed that the Pt nanoparticles and carbon trapped in pores and spread evenly on the fibers of BC.…”
Section: Introductionmentioning
confidence: 99%